2021
DOI: 10.1037/neu0000720
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and psychosocial mechanisms underlying racial/ethnic disparities in cognition among older adults.

Abstract: Objective: Racial/ethnic disparities in cognitive aging are only partly attributable to socioeconomic indicators. Psychosocial factors, such as discrimination and perceived control, also differ across racial/ ethnic groups, and emerging literature highlights their potential role in contributing to cognitive disparities in addition to socioeconomic status. Method: 1,463 older adults (51% Hispanic, 27% non-Hispanic Black, and 22% non-Hispanic White) in the Washington Heights-Inwood Columbia Aging Project complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 105 publications
5
36
0
Order By: Relevance
“…60 Although this review specifically examined race/ethnicity, we acknowledge that race is a social construct and that health disparities are often driven by social determinants of health, such as education, literacy, socioeconomic status, racially patterned social stress, and access to care. [61][62][63] Although some trials in this review with race/ethnicity data reported the education level of the included participants, none mentioned SES. This limited reporting of social determinants of health is in line with a previous review in symptomatic treatment of AD, in which no studies reported on variables such as lifetime occupation, individual/household income, or wealth, and few studies on education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Although this review specifically examined race/ethnicity, we acknowledge that race is a social construct and that health disparities are often driven by social determinants of health, such as education, literacy, socioeconomic status, racially patterned social stress, and access to care. [61][62][63] Although some trials in this review with race/ethnicity data reported the education level of the included participants, none mentioned SES. This limited reporting of social determinants of health is in line with a previous review in symptomatic treatment of AD, in which no studies reported on variables such as lifetime occupation, individual/household income, or wealth, and few studies on education.…”
Section: Discussionmentioning
confidence: 99%
“…Although this review specifically examined race/ethnicity, we acknowledge that race is a social construct and that health disparities are often driven by social determinants of health, such as education, literacy, socioeconomic status, racially patterned social stress, and access to care 61–63 . Although some trials in this review with race/ethnicity data reported the education level of the included participants, none mentioned SES.…”
Section: Discussionmentioning
confidence: 99%
“…The research found that ethnic discrimination is a risk factor for psychotic disorders (Bardol et al, 2020). Discrimination's negative impacts on cognition in different age groups are well documented (e.g., Díaz-Venegas et al, 2016;Zahodne et al, 2021;Kira et al, 2020d).…”
Section: Identity (Personal and Collective) Trauma Modelmentioning
confidence: 99%
“…In studies considering both discrimination and external control as separate, simultaneous mediators, external control has consistently emerged as a stronger contributor to racial inequalities in cognitive aging outcomes (Zahodne et al, 2017; Zahodne et al, 2021). In addition, external control shows much more reliable Latinx–White differences than discrimination (Zahodne, Sol & Kraal, 2019; Zahodne et al, 2021), as Latinx older adults often report less everyday discrimination than Whites (Lewis et al, 2012; Zahodne et al, 2021). This pattern of results might suggest that measures of external control capture the cognitively-relevant psychosocial experiences of marginalized social groups better than commonly-used measures of everyday discrimination.…”
Section: Biopsychosocial Explanations For Persistent Inequalitiesmentioning
confidence: 99%